Awareness of Polycystic Ovarian Syndrome among Jordanian Females - Barrouq, Deena M. S.; Zaineh Faisal Rasheed Alazawa; Tareq Irshaidat (HM Publisher, 2023)
Many endocrine-related conditions have attracted the attention of medical societies worldwide. Many of them may have a serious impact on female re-productivity and overall health. Among them is the polycystic ovarian syndrome (PCOS). However, an early diagnosis is crucial in avoiding any potential complications. This study aimed at evaluating the awareness of PCOS among Jordanian females. The outcomes shall be implemented to improve public health through the various educational services, medical campaigns, and healthcare practitioners in Jordan and other societies. A cross-sectional study using a survey (questionnaires) was directed toward a sample of Jordanian females aged 18-40 years. The assessment of their knowledge and understanding included its signs, symptoms, and associated health risks. Thus, the collected data were subject to processing and statistical analysis. The majority of females (73.3%) were aware of the potentiality of PCOS, but the majority of the sample was not satisfactorily familiar with the signs and symptoms of the disease, and only 6% confirmed getting education directly from a doctor. The study outcome reveals that the current level of PCOS awareness among Jordanian females needs a comprehensive educational effort.